Influence of Vitamin C on Mouse Vital Organ Mercuric Chloride Toxicity - Saranya Soni (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
The present study was undertaken to investigate the ability of antioxidants (Vitamin C and E) to protect against mercuric chloride induced testicular toxicity in male mice during pre pubertal phase of life. A sublethal chronic exposure (0.5 ml/day of 0.5 ppm aqueous HgCl2) resulted in regressed histological properties of the testis. The changes observed were broken and detached tunica albuginea, abnormal configuration of seminiferous tubules, deformed primary and secondary spermatocytes, hypertrophy and vacuolization in Leyding cells and Sertoli cells. The diameter of different spermatogenic cells were significantly (P<0.001) decreased. These changes were ameliorated with the administration of vitamin C and E. The results of our study suggested that antioxidant vitamin C and vitamin E exert significant protection against histological damage of testes induced by mercury and provide a strong evidence for the beneficial role of antioxidant vitamins in prevention of mercury toxicity.